Assessing the active aging index in Uzbekistan: Employment, social engagement, and well-being - Egamberdiyeva, Nodira; Khamid, Abdurahmanov; Ruzieva, Gavhar; Yulchiyeva, Dildora; Rahmanova, Gulchehra (Edelweiss Applied Science and Technology, 2025)
This article presents the findings of a study evaluating the Active Aging Index (AAI) in Uzbekistan, conducted by specialists from the Research Institute "Family and Gender" in collaboration with the National Institute of Economic Research of Moldova, with financial support from the United Nations Population Fund (UNFPA). The study aims to assess the status and challenges of active aging in Uzbekistan by analyzing employment trends, social participation, independent and secure living conditions, and the broader enabling environment for aging. Since 2012, the Active Aging Index has been widely used in European Union countries as a comprehensive indicator and policy monitoring tool. Applying this methodology to Uzbekistan, the study investigates demographic shifts, economic participation, access to social and healthcare services, and overall quality of life among older adults. The findings reveal significant challenges, including low employment rates among the elderly, limited access to healthcare, economic insecurities, and insufficient social support mechanisms. Additionally, the research highlights regional and gender disparities in aging experiences, with rural and female elderly populations facing greater socio-economic vulnerabilities. Given the lack of complete statistical datasets, the study incorporates proxy indicators to ensure a more accurate assessment. The results emphasize the need for targeted policy interventions to enhance employment opportunities, improve healthcare access, and develop comprehensive social protection programs for older adults. The study concludes with recommendations aimed at strengthening Uzbekistan’s active aging framework to promote a higher quality of life and greater social inclusion for the elderly.